Efektivitas Tayangan Politik PKSTV dalam Meningkatkan Dukungan Pemilih PKS pada Pemilu 2024 - Oktavia Anggi Ramadhani; Khansa Nabilla Lutfiyah; Rahma Titania; Ahren Jasmine Azzahra; Muhammad Prakoso Aji (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to analyze the effectiveness of PKSTV, a digital television platform owned by the Prosperous Justice Party (PKS), in increasing voter support in the 2024 election. The study focuses on how PKSTV, as a digital political campaign medium, plays a role in shaping public perception and influencing voters’ political behavior. Using a qualitative approach, this research employs literature review and content analysis to examine PKSTV’s political communication strategies, including the application of Agenda Setting Theory, in highlighting key issues and building a positive public opinion of PKS. The findings show that PKSTV contributes to increasing voters’ knowledge of PKS (cognitive effect), establishing a positive image of PKS among the public (affective effect), and mobilizing voter support (behavioral effect). However, PKSTV also faces challenges from intense competition in the digital media landscape and political polarization. The conclusion of this study indicates that PKSTV has significant potential to support PKS’s voter mobilization strategy through interactive and relevant digital content, especially for younger voters.